An Information Technology Service Hub for Effective Service Delivery in Nigeria - , Okpalla, C. L., Eke, C. A., Onukwugha, C. G., Iwuchukwu, V.C., Nwokoma, F. O., Onwuama, T. U. (Archives of Current Research International, 2023)
This paper aims at supporting freelancing and self-employment among information technology service providers, particularly newcomers, by allowing them to use the internet's broad reach to find jobs both inside and outside their location. The ongoing growth in unemployment in Nigeria has impacted every sector of the economy, including the delivery of information technology services. There are many skilled persons in the industry, but possibilities appear to be limited. This is due to the lack of specific platforms for information technology service providers to offer their services, which makes it difficult for potential clients to find a service provider to accomplish their work. This dilemma prompted the construction of a dedicated platform, which would serve as a one-stop shop for both an information technology service provider and a potential client, bridging the gap between them. The object oriented analysis and design methodology (OOADM) was employed in this research, and HTML, CSS, PHP, MySQL, and JavaScript were used to design the application in order to achieve a high level of scalability and platform performance. It is simple to use and allows service providers on the platform to operate freely without being charged a percentage of their earnings. This paper will be of immense benefit to the unemployed, masses and the Government.